Seasonal and spatial dynamics of enteric viruses in wastewater and in riverine and estuarine receiving waters - Farkas, Kata; Cooper, David M.; McDonald, James E.; Malham, Shelagh K.; de Rougemont, Alexis; Jones, Davey L. (The Science of the total environment, 2018)
Enteric viruses represent a global public health threat and are implicated in numerous foodborne and waterborne disease outbreaks. Nonetheless, relatively little is known of their fate and stability in the environment. In this study we used carefully validated methods to monitor enteric viruses, namely adenovirus (AdV), JC polyomavirus (JCV), noroviruses (NoVs), sapovirus (SaV) and hepatitis A and E viruses (HAV and HEV) from wastewater source to beaches and shellfish beds. Wastewater influent and effluent, surface water, sediment and shellfish samples were collected in the Conwy catchment (North Wales, UK) once a month for one year. High concentrations of AdV and JCV were found in the majority of samples, and no seasonal patterns were observed. No HAV and HEV were detected and no related illnesses were reported in the area during the period of sampling. Noroviruses and SaV were also detected at high concentrations in wastewater and surface water, and their presence correlated with local gastroenteritis outbreaks during the spring and autumn seasons. Noroviruses were also found in estuarine sediment and in shellfish harvested for human consumption. As PCR-based methods were used for quantification, viral infectivity and degradation was estimated using a NoV capsid integrity assay. The assay revealed low-levels of viral decay in wastewater effluent compared to influent, and more significant decay in environmental waters and sediment. Results suggest that AdV and JCV may be suitable markers for the assessment of the spatial distribution of wastewater contamination in the environment; and pathogenic viruses can be directly monitored during and after reported outbreaks to prevent further environment-derived illnesses. [Display omitted] •The TFUF concentration method is suitable for quantifying viruses in water samples.•For the first time, sapovirus was found in UK waters.•Enteric viruses were traceable from source to beaches and shellfish beds.•Norovirus concentrations in the environment agreed with local outbreaks.•PGM assay is useful to study norovirus degradation in the environment.